The Art of Giving - Through Volunteerism and Philanthropy: The Ghana Experience - Aryeetey, E.B.; Opai-Tetteh, D.D. (Center for Social Policy Studies - University of Ghana, 2012)
The world has known a long history of philanthropy and volunteerism, in spite of its centuries of wars and often acrimonious social relations between adversaries. Traditional giving practices were and remain predominantly in the form pf reciprocal exchange ,of goods and services between kin groups and their neighbours to sustain social capital. The objective of this working paper is to review the nature and practice of giving in general, but with special reference to Ghana. The aim is mainly to introduce the development community to the importance of social mobilization in the overall efforts at social progress by highlighting the contributions that charitable giving can make to social development. In the process the paper unveils some of the challenges that confront giving in Ghana. The discussion points out that while familial giving receives a lot of attention in the country, there is a growing incidence of civic giving taking place; some of it with support from public institutions, Having said that, it does appear that the scene is dominated by customary giving practices, which leave a lot of scope for advancing civic forms of giving. Religious beliefs, philosophical ideas and ethical principles have all contributed to the endurance of societal commitment to reciprocity and redistribution. The United Nations General Assembly in 1985 set aside 5th December every year to celebrate the International Volunteer Day. This has further created renewed interest in volunteer activities across the world. The paper relies mainly on secondary data on giving in Ghana and elsewhere. The main finding is that in developed economies where attractive policies are in place to encourage people to give to charity huge amounts of funds can be mobilized for charity work. On the other hand in countries like Ghana though giving is common, especially as remittances and for funerals, philanthropy and volunteerism are largely unstructured and informal. . In addition, data on the scope and value of such practices is virtually non-existent, making it difficult to mobilize such funds for planned social development.
Working Paper
Keywords: Art; Giving; Philanthropy; Volunteerism